Establishment of a human cell line with a surface display system for screening and optimizing Na+-taurocholate cotransporting polypeptide-binding peptides - Wang, Pei-yun; Yang, Xue; Guo, Lin; Wang, Yu-wei; Zhang, Wen-lu; Sun, Yu-xue; Li, Jie; Gan, Chun-yang; Long, Shao-yuan; Liu, Jia-jun; Fan, Shu-ying; Huang, Ai-long; et al. (Frontiers in Microbiology, 2022)
Peptides targeting membrane protein receptors are an important source of antiviral drug candidates. However, screening these peptides in commonly used surface display systems may be difficult. These peptides frequently require modifications to function, and their targeting membrane protein receptors are often challenging to express and purify. To address these two problems, we propose a strategy of peptide screening method based on human cell surface display, and we used the optimization of peptides targeting Sodium Taurocholate Co-transporting Polypeptide (NTCP), the receptor of Hepatitis B virus (HBV), as an example to demonstrate the strategy. First, we extended seven random amino acids based on preS1 2-21 fused with mCherry and FasL transmembrane domain and employed transposon/transposase to create a HEK293 cell whose surface displays a polypeptide library. Then, we expressed NTCP protein fused with EGFP on HEK293 and used the membrane lysate containing NTCP-GFP as bait protein to select mutants with increased NTCP affinity. After 7 cycles of selection, the deep sequencing results revealed that some polypeptides were more than 1000 times enriched. Further testing of 10 peptides with the highest enrichment degree yields the peptides 217-3. In tests on the HepG2-NTCP cell model, Myr217-3 synthesized in vitro was 10 times more potent than the initial peptide Myr21 at preventing HBV infection. These results validated the screening system's efficiency and served as a guide for developing peptides that target other viral receptors.